Predicting non-small-volume central lymph node metastases (>5 or ≥2 mm) preoperatively in cN0 papillary thyroid microcarcinoma without extrathyroidal extension. Issue 38 (18th September 2020) - Shou, Jin-Duo; Li, Fei-Bo; Shi, Liu-Hong; Zhou, Liang; Xie, Lei; Wang, Jian-Biao
Abstract : Abstract: The ability to identify patients with aggressive papillary thyroid microcarcinoma (PTMC) from the low-risk patients is critical to planning proper management of PTMC. Lymph node metastases showed association with recurrence and low survival rate, especially in patients with >5 or ≥2 mm metastatic lymph nodes. Therefore, this study aimed to investigate the preoperatively predictive factors of non-small-volume (metastatic lymph nodes >5 or ≥2 mm in size) central lymph node metastases (NSVCLNM) in PTMC patients. A total of 420 patients with clinically node-negative (cN0) PTMC without extrathyroidal extension underwent thyroidectomy plus central neck dissection (CND) between January 2013 and December 2015, were retrospectively analyzed. Of the 420 patients, 33 (7.9%) had NSVCLNM. The 5-year recurrence-free survival was significantly less in cN0 PTMC patients with NSVCLNM, when compared with patients without NSVCLNM (80.8% vs 100%, P  < .001). Multivariate logistic regression revealed age ⩽36 years ( P  < .001), male sex ( P  = .002), ultrasonic tumor sizes of >0.65 cm ( P  < .001), and ultrasonic multifocality ( P  = .039) were independent predictive factors of NSVCLNM. A prediction equation (Y = 1.714 × age + 1.361 × sex + 1.639 × tumor size + 0.842 × multifocality −5.196) was developed, with a sensitivity (69.7%) and a specificity (84.0%), respectively, at an optimal cutoff point of −2.418. In conclusion, if the predictive value was >−2.418 according to the equation, immediate surgery including CND rather than active surveillance might be considered for cN0 PTMC patients.